Exploring new methods to analyse spatial impact distributions on debris‐flow fans using data from south‐western British Columbia. Issue 12 (20th July 2021) - Zubrycky, Sophia; Mitchell, Andrew; McDougall, Scott; Strouth, Alex; Clague, John J.; Menounos, Brian
Abstract: Predicting the spatial impact of debris flows on fans is challenging due to complex runout behaviour. Debris flow mobility is highly variable and flows can sporadically avulse the channel. For hazard and risk assessments, practitioners typically base the probability of spatial impact or avulsion on their experience and expert judgement. To support decision‐making with empirical observations, we studied spatial impact distributions on 30 active debris‐flow fans in south‐western British Columbia, Canada. We mapped 146 debris‐flow impact areas over an average observation period of 74 years using orthorectified airphotos, satellite imagery, topographic base maps, LiDAR data, orthophotos, and field observations. We devised a graphical method to convert our geospatial mapping into spatial impact heat maps normalized by fan boundaries, enabling comparison of runout distributions across different fans. About 90% of the mapped debris flows reached beyond the mid‐points of fans, while less than 10% avulsed more than half‐way across the fan relative to the previous flow path. Most avulsions initiated at distances of 20% to 40% of the maximum fan length from the fan apex and upstream of the fan intersection point. Large volume events tend to be more mobile in the down‐fan direction, but the relation between volume and cross‐fan runout (e.g., avulsions) is more complex. Differences in spatial impact distributions can be explained, in part, by the degree of fan incision and whether a fan is truncated at its toe by a river or lake. There were no significant differences in spatial impact distributions based on the geology of the source area, sediment supply condition, or hydrogeomorphic process classification. Abstract : We present a graphical method to convert debris‐flow impact mapping into spatial impact heat maps normalized by fan boundaries, enabling comparison of runout distributions across different fans. Based on mapping of debris‐flow runout on 30 active fans in south‐western British Columbia, we found that 90% of the mapped debris flows reached beyond the mid‐points of fans, while less than 10% avulsed more than half‐way across the fan relative to the previous flow path.